2018
DOI: 10.1007/s00253-018-8812-0
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of the mitochondrial genome of the fungus Colletotrichum lindemuthianum, the causal agent of anthracnose in common beans

Abstract: Fungi of the genus Colletotrichum are economically important and are used as models in plant-pathogen interaction studies. In this study, the complete mitochondrial genomes of two Colletotrichum lindemuthianum isolates were sequenced and compared with the mitochondrial genomes of seven species of Colletotrichum. The mitochondrial genome of C. lindemuthianum is a typical circular molecule 37,446 bp (isolate 89 A 2-3) and 37,440 bp (isolate 83.501) in length. The difference of six nucleotides between the two gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 58 publications
0
13
0
Order By: Relevance
“…These features make it suitable for distinguishing closely related species or even intra-specific isolates, as well as deduction of recent evolutionary events. Intra-specific mtDNA comparison has been used in fungal species such as Cordyceps militaris [24] , Schizosaccharomyces pombe [25] , Isaria cicadae [10] , and Colletotrichum lindemuthianum [26] . These studies provided new insights into population evolution, identification of highly polymorphic regions, and isolate-specific markers [24] .…”
Section: Introductionmentioning
confidence: 99%
“…These features make it suitable for distinguishing closely related species or even intra-specific isolates, as well as deduction of recent evolutionary events. Intra-specific mtDNA comparison has been used in fungal species such as Cordyceps militaris [24] , Schizosaccharomyces pombe [25] , Isaria cicadae [10] , and Colletotrichum lindemuthianum [26] . These studies provided new insights into population evolution, identification of highly polymorphic regions, and isolate-specific markers [24] .…”
Section: Introductionmentioning
confidence: 99%
“…2017; de Queiroz et al . 2018), but was not observed in N. crassa . Nevertheless, the start codon of nd2 is immediately after the stop codon of nd3 with no intergenic sequence between both genes.…”
Section: Resultsmentioning
confidence: 89%
“…2008) and Colletotrichum lindemuthianum (de Queiroz et al . 2018). The longest overlap (658 bp) occurs between NADH dehydrogenase subunit 4 and a laglidadg endonuclease.…”
Section: Resultsmentioning
confidence: 99%
“…of Colletotrichum species are due, in part, to the presence or absence of ncORFs and intronic sequences [66]. The large mtDNA size of Phlebia radiata (156 kbp) also harbors a large number of introns and long intergenic regions [63].…”
Section: Plos Onementioning
confidence: 99%
“…Many of the ncORFs were related to HEGS, primarily LAGLIDADG endonucleases. Queiroz et al [66] observed that C. lindemuthianum contains just one intronic ncORF encoding a LAGLIDADG endonuclease. However, more than one intronic ncORF encoding LAGLIDADG endonucleases were found in rust mtDNA.…”
Section: Plos Onementioning
confidence: 99%